Sports-related injuries of the biceps and triceps - Bain, G. I.; Durrant, A. W. (Clinics in Sports Medicine, 2010)
Biceps or triceps ruptures are rare but can cause a significant disability. Surgical repair has become the preferred method of treatment for the complete rupture, but the decision when to treat partial tears is less clear. Reconstruction of the tendon is the preferred method when patients have a delayed presentation